2020
DOI: 10.3390/ijerph17093032
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value Estimation of the Natural Heritage of the Tatra National Park

Abstract: The aim of the study is to determine the economic value of the Tatra National Park. The willingness to pay approximation was used. Additionally, a questionnaire survey was applied in order to collect data. It contained a hypothetical event, and respondents expressed their willingness to pay an annual entry fee to the Tatra National Park in exchange for a guarantee of stopping the interference to its integrity. The total number of respondents was 921. The results show that the income level has a positive impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…The findings also suggest that residents who better made choices of improved ecological conservation were those who had more income sources, were older in age and had more family laborers. This finding is consistent with the study by [ 67 ] who reported that income level and age of respondents had significant impact on WTP for the conservation of the natural heritage in Tatra National Park. Sex, size of land holding, and the number of oxen owned appeared with negative coefficients, implying that residents owning a greater number of oxen involved in cultivation of food crops preferred assigning a larger share of their plots to cultivation of food crops, than to plantation of Eucalyptus .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings also suggest that residents who better made choices of improved ecological conservation were those who had more income sources, were older in age and had more family laborers. This finding is consistent with the study by [ 67 ] who reported that income level and age of respondents had significant impact on WTP for the conservation of the natural heritage in Tatra National Park. Sex, size of land holding, and the number of oxen owned appeared with negative coefficients, implying that residents owning a greater number of oxen involved in cultivation of food crops preferred assigning a larger share of their plots to cultivation of food crops, than to plantation of Eucalyptus .…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the benefits from the exclusion of fertile plots from plantations and increasing the number of other tree species were USD 24.35/person/year and USD 125.82/person/year, respectively; the overall value being USD 205. Differences in attribute values have also been reported by [ 67 ].…”
Section: Discussionsupporting
confidence: 63%
“…Intuitively, the expected effect is that more visits to PAs in the past will lead to a positive effect on the WTP [30,31]. However, in this study, we found the opposite-the respondents who have visited PAs more frequently have a lower WTP.…”
Section: Relationship Between the Number Of Visitations And Wtpcontrasting
confidence: 57%
“…The effect of most variables on WTP for visiting PAs aligns with previous studies. The profile of potential users of this type of product shows consistency, and in general, it has been demonstrated that younger people with higher levels of education and income are the population that are most interested and willing to pay [29,30], as well as those who have visited protected areas before [29,31] and those who are aware of the importance of conserving protected areas to preserve resources and biodiversity [29,31]. In this sense, this study corroborates other studies' findings regarding the feasibility of a one-year passport.…”
Section: Willingness To Pay For Environmental Conservationmentioning
confidence: 99%